METHODOLOGY OF CHEMISTRY. - Badalboyeva Dilorom Sobirjon qizi; Qo’shaqov Doniyorbek Abdumutal o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article is about the fact that the methodology of teaching chemistry is a scientific and educational science, the methodology of teaching chemistry is closely related to the science of pedagogy and its educational function is based on the laws of pedagogy